Addressing Conflicts of Interest and Conflicts of Commitment in Public Advocacy and Policy Making on CRISPR/Cas-Based Human Genome Editing - Christian, Alexander (Frontiers in Research Metrics and Analytics, 2022)
Leading experts on CRISPR/Cas-based genome editing—such as 2020 Nobel laureates Jennifer Doudna and Emmanuelle Charpentier—are not only renowned specialists in their fields, but also public advocates for upcoming regulatory frameworks on CRISPR/Cas. These frameworks will affect large portions of biomedical research on human genome editing. In advocating for particular ways of handling the risks and prospects of this technology, high-profile scientists not only serve as scientific experts, but also as moral advisers. The majority of them currently intend to bring about a “responsible pathway” toward human genome interventions in clinical therapy. Engaging in advocacy for such a pathway, they issue moral judgments on the risks and benefits of this new technology. They declare that there actually is a responsible pathway, they draft resolutions on temporary moratoria, they make judgments on which groups and individuals are credible and should participate in public and semi-public debates, so they also set the standards for deciding who counts as well-informed, as well as the standards of evidence for adopting or rejecting research policies. This degree of influence on public debates and policy making is, at the very least, noteworthy. This contribution sounds a note of caution with regard to the endeavor of a responsible pathway to human genome editing and in particular scrutinizes the legitimacy of expert-driven research policies given commercial conflicts of interest and conflicts of commitment among first-rank scholars.